Forecasting the renewable energy consumption of the European countries by an adjacent non-homogeneous grey model - Liu, Lianyi; Wu, Lifeng (Applied Mathematical Modelling, 2021)
In this paper, a new adjacent non-homogeneous grey model was proposed to predict renewable energy consumption in Europe. Based on the principle of adjacent accumulation, the proposed model emphasizes the weight relationship between the latest value and the historical data. Meanwhile, the heuristic algorithm is used to optimize the parameters of the proposed model. The model's performance was tested by the examples from four central European countries, including Austria, the Czech Republic, Hungary and Poland. In addition, the consumption of renewable energy in Europe and the world was predicted respectively, which showed that Europe's proportion of the world's renewable energy consumption will gradually decline.